French romanesque Bibles in Portugal: the “Codex Capituli Ecclesiae B. Mariae Vernonensis” - Van Binnebeke, Xavier (2019)
This article investigates an imposing Romanesque Bible set from France that has hitherto escaped the attention of manuscript researchers. The two volumes, kept in the Biblioteca da Ajuda in Lisbon, are among the oldest illuminated manuscripts preserved in Portugal. The early provenance history of the Bible can be pointed out thanks to the analysis of a series of mediaeval inscriptions present on the flyleaves and concerning, i.a., the deeds of King Philippe August and the translation of a relic of Saint Maximus. In addition, the later history of this exceptional set can be reconstructed in detail on the basis of a variety of early modern sources, including several historical catalogues of the library of the Necessidades Convent in Lisbon. The article will also describe and discuss the fine illumination, and seek to position the volumes within the development of Romanesque Bible production.